2011
DOI: 10.1016/j.sdentj.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Canine location in different maxillomandibular relationships in Egyptians and Saudis

Abstract: Commissures are not a reliable landmark for determination of the distal aspect of the canine distal aspects of both Egyptian and Saudi populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, this was not in accordance with other authors who either found it to be nonsignificant or not related. 13,23,25,26 This contradiction can be related to various methodologies used for measurement of either ICoW or intercanine distance. Width/Length (W/L) ratios of the anterior teeth are related to the anterior esthetics.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not in accordance with other authors who either found it to be nonsignificant or not related. 13,23,25,26 This contradiction can be related to various methodologies used for measurement of either ICoW or intercanine distance. Width/Length (W/L) ratios of the anterior teeth are related to the anterior esthetics.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted on 226 Saudi students who reflect a diverse mix of Arab populations as a result of immigration and settlement in Saudi Arabia 25 . In this study, the IC line, rather than the line joining the most distal points of the canines, was used for measurements.…”
Section: Discussionmentioning
confidence: 99%